Governança em aglomerações produtivas: o caso das cervejas artesanais da microrregião de Juiz de Fora - MG - Vargas, Laura Junqueira (2019)
Productive agglomerations have been a great way specially for small business to overcome barriers for their survival and to gain in efficiency and competitiveness. In Brazil, the term Local Productive Arrangement (APL) was popularized as an instrument of regional economic development focused on small companies. Among the factors that enable the maintenance and development of these arrangements are the mechanisms of governance that, despite of their polysemic nature, can be synthetized as a process of coordination that seeks to reconcile the interests of different actors. Considering the essentiality of governance for the existence of an APL and its commitment to align collective interests, it is important to develop studies that contemplate this theme. Consequently, this study was developed with the purpose of verifying the role of the supporting institutions and the public power in the governance process and territorial development of the APL of craft beers of Juiz de Fora (Brazil) and its microregion. For that, a qualitative research was adopted, and 14 representatives of the three main groups of actors of the APL studied were interviewed, namely: the brewery entrepreneurs, the representatives of the supporting institutions and the representatives of the public power. In addition to field research, bibliographic and desk research were also used. The theoretical background addressed the two main themes of the study: productive agglomerations, focusing on APLs, and governance, especially when related to these agglomerations. Although many theoretical contributions were found, it was possible to develop a theoretical model that would help to understand which factors contribute to the development of governance in a productive agglomeration, enabling its progress from early to advanced stage, addopting the idea of a spiral. As a result, it was observed that the governance in the APL studied is still incipient, with a lack of interest, participation and articulation between the actors that are part of it. It is noticed that these actors are already aware of the factors that hinder the APL development, making it necessary that this awareness becomes concrete actions. Many actions are still in need of being undertaken to speed an effective development of governance in the studied APL.